2013
DOI: 10.1177/0748233713491804
|View full text |Cite
|
Sign up to set email alerts
|

The effect of occupational lead exposure on lipid peroxidation, protein carbonylation, and plasma viscosity

Abstract: The aim of the study was to investigate the influence of occupational lead (Pb) exposure on lipid peroxidation, protein carbonylation, and plasma viscosity in workers. The examined group included 283 healthy male employees of manufacturing facilities using zinc and Pb. The mean blood concentrations of Pb and zinc protoporphyrin as well as the mean urine δ-aminolevulinic acid levels were used as markers of exposure for the examined group. Taking into account the obtained mean values of blood lead level, the exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 35 publications
2
10
0
1
Order By: Relevance
“…The results of this study show that urine lead levels are positively correlated with triglycerides, which is consistent with the experimental conclusions reached by Park YJ et al [17]. Previous studies observed that lipid peroxidation could be caused by occupational lead exposure, and occupational lead exposure induced oxidative stress that resulted in lipid damage [18,19], a finding similar to the results of this study. Another study also found that early-life exposure to lead was strongly correlated with obesity, which was consistent with our results showing that urine lead content had a close positive correlation with lipid metabolism [20].…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study show that urine lead levels are positively correlated with triglycerides, which is consistent with the experimental conclusions reached by Park YJ et al [17]. Previous studies observed that lipid peroxidation could be caused by occupational lead exposure, and occupational lead exposure induced oxidative stress that resulted in lipid damage [18,19], a finding similar to the results of this study. Another study also found that early-life exposure to lead was strongly correlated with obesity, which was consistent with our results showing that urine lead content had a close positive correlation with lipid metabolism [20].…”
Section: Discussionsupporting
confidence: 93%
“…The level of thiol groups is the 2nd measured parameter indirectly reflects oxidative stress intensity. In our previous study, we reported significantly decreased thiol groups level in a similar group of workers who were exposed to lead (26). Results of the present study indicate that β-carotene is efficient to restore the level of thiol groups.…”
Section: Discussionsupporting
confidence: 68%
“…One study measured the production of isoprostane to check the oxidation of tissue phospholipids and observed increased isoprostane levels in welders when compared with the control group; it also identifi ed that age and cigarette smoking did not contribute to the 2.4-fold increase in the isoprostane levels observed in welders (Han et al 2005 ). Two studies analyzed conjugated dienes, a primary end-product of LPO and both reported a positive correlation with BLLs (r = 0.33; p < 0.05 and r = 0.694; p < 0.001) (Permpongpaiboon et al 2011 ;Kasperczyk et al 2013c ).…”
Section: Lead-induced Oxidative Stress In Occupationally Exposed Popumentioning
confidence: 87%